Pengembangan Manajemen Pendidikan Karakter dengan Whole School Development Approach (WSDA) di MTs. Babussalam Tambar Jombang - Eko Hadi Wardoyo; Agung Prakoso (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2018)
This study aims to determine Character Education Management Development with the Whole School Development Approach (WSDA) in MTs. Babussalam Tambar Jogoroto Jombang using a qualitative approach. This is based on the intention to describe a concrete social reality, so that it is in accordance with the research and its implementation involving the leadership and all available education personnel. This type of research is qualitative descriptive. In this study the data collection techniques used were observation (participant observation), interviews and document techniques (document study). While the data analysis uses qualitative descriptive analysis, namely research data that has been collected, both qualitative data (in the form of exposure to words or sentences) and quantification data (in the form of numbers) will be processed with qualitative descriptive analysis techniques. The results of this study indicate that the development of character education management with the Whole School Development Approach (WSDA) in MTs. Babussalam Tambar Jogoroto Jombang has gone well. This is proven by involving the role and responsibility of all components of education in schools and the participation of parents at home.